Seeking outcomes under tight budgets: a case for health impact bonds in post-COVID times - Shiva, M (Wiley, 2023)

(untitled)
With global public debt at record levels, governments are facing unprecedented challenges in providing essential health services. This exploratory study aims to assess the relevance of Health Impact Bonds (HIBs) as a means of financing preventative health services during times of fiscal constraint and in the aftermath of the COVID pandemic. The study draws on a review of the literature on HIBs, along with a case study analysis of HIBs implemented in the UK. The findings of the study indicate that, although HIBs offer promise as an innovative funding tool for preventative health services in tight fiscal situations, certain challenges are limiting their broader adoption.